2019
DOI: 10.1001/jamanetworkopen.2019.4585
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Cessation Counseling, Prescription Medication Use, and Associated Costs Among US Adult Cigarette Smokers

Abstract: Key Points Question What are the 10-year trends in the delivery of cigarette smoking cessation services for adult smokers in the United States? Findings In this cross-sectional study of 29 106 US adult smokers from 2006 to 2015, the proportion who reported receiving physician advice to quit smoking increased and the use of prescription cessation medication decreased with a corresponding reduction in expenditures. Lower rates of cessation services were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…More broadly, equitable access to and coverage of tobacco-cessation treatment is needed to serve minorities and vulnerable populations ( 105 , 106 ). Although racial and ethnic minority groups are more likely than white individuals to attempt smoking cessation, they are less likely to be advised to quit smoking and to be offered behavioral counseling and pharmacotherapy and thus have lower odds of success ( 107 ).…”
Section: Resultsmentioning
confidence: 99%
“…More broadly, equitable access to and coverage of tobacco-cessation treatment is needed to serve minorities and vulnerable populations ( 105 , 106 ). Although racial and ethnic minority groups are more likely than white individuals to attempt smoking cessation, they are less likely to be advised to quit smoking and to be offered behavioral counseling and pharmacotherapy and thus have lower odds of success ( 107 ).…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis of the changes in cigarette smoking cessation counseling among US adult cigarette smokers, the proportion who reported receiving physician advice to quit smoking has increased. 5 Cancer diagnosis represents a teachable moment 3 , 4 , 23 : advice from a clinician about the health benefits of quitting can promote cigarette smoking cessation. Despite this progress at the population level, smoking prevalence among cancer survivors remains high.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Considerable progress has been made in reducing cigarette smoking in the United States, and the proportion of smokers who reported receiving physician advice to quit has increased over the last decades. 5 However, the prevalence of cigarette smoking among cancer survivors remains high. 2 , 6 , 7 A recent cross-sectional analysis of the 2017 National Health Interview Survey (NHIS) data reported that 13.2% of US adult cancer survivors were current smokers, 7 but trends in cigarette smoking cessation among cancer survivors have not yet been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while in USA, it was not common for physicians to address patients' smoking in 1990s and 2000s, 21 then in 2018, 65% of patients were asked about smoking status. 22 In Romania in 2011, more than 80% of patients were asked about their smoking status. 1 In 2009-2010, in Poland, 57.2% and in Russia, 45.4% of patients reported that they were asked if they smoked by a health care provider.…”
Section: Discussionmentioning
confidence: 99%